Detection of the ethiologic agents of the childhood acute gastroenteritis - Kizirgil, Ahmet; Karakoç, Selahattin (My University, 2012)
Objective: Acute gastroenteritis which is a significant mortality and morbidity cause for children remains a global public health problem. In this study, the infectious agents of the childhood gastroenteritis are investigated in Elazig region, Turkey. Material and Method: Acute gastroenteritis agents were investigated in the stool samples which were obtained from a total of 407 children aged 0-14 years, who were admitted to Pediatrics Clinics of Firat University Hospital between 01 fanuary and 31 December 2008. Campylobacter, Shigella and Salmonella strains were investigated with culture methods, antigens of Rotavirus and Adenovirus were with immunochromatographic tests while parasitic Results: Of the stool samples, viral, parasitic and bacterial agents were found to be 36.4%, 11.3% and 7.6%, respectively. However, no ethiologic agent was identified in 44.7% of the toted samples. The most frequently observed pathogenic agent was rotavirus (31.9%). The rank order of the other etiologic agents of gastroenteritis was as follows: Giardia intestinalis (G. intestinalis) (10.1%), Campylobacter spp. (4.7%), enteric adenoviruses (4.4%), Shigella spp. (2%), Entamoeba histolytica (E. histolytica) (1.2%) and Salmonella spp. (1%). Conclusion: Rotaviruses should be kept in mind for the childhood gastroenteritis in our region, and diagnostic and therapeutic approaches may be planned according to other pathogens and their frequency.
Çocukluk Yaş Grubu Akut Gastroenteritlerinde Etyolojik Ajanlarin Belirlenmesi
Keywords: Adenovirus; Campylobacter; Gastroenteritis; Giardia; Rotavirus